2015
DOI: 10.1080/15384101.2015.1064203
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of PKM2 modulates astrocyte proliferation via p27 and β-catenin pathway after spinal cord injury

Abstract: Department of Stomatology; Affiliated Hospital of Nantong University, Nantong; Nantong University; 226001, Nantong, Jiangsu, PR China y These authors equally contributed to this work, and should be considered as joint first authors.Keywords: astrocyte proliferation, b-catenin, p27, PKM2, spinal cord injuryAbbreviations: CNS, Central nervous system; CDKs, cyclin-dependent kinases; CAK, CDK activating kinase; E2F, E2 promoter-binding protein dimerization partners; GFAP, Glial fibrillary acidic protein; GAPDH, Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…The data presented here show that in control cells, pY-containing HuR is predominantly a nuclear protein, and that forms of PKM2 that retain pY-binding ability co-immunoprecipitate with HuR as well as rescue cells from defects in cell cycle progression caused by PKM2 knock-down. The accumulation of HuR in the cytoplasm following suppression of PKM2 levels also supports the idea that PKM2 binds and traps HuR, and in particular pY-containing HuR (as well as possibly p27 itself) 47 in the nucleus, limiting the ability of HuR to facilitate p27 mRNA translation in the cytoplasm. Under these conditions the trapped nuclear HuR may be able to function as a progrowth regulator of splicing and a stabilizer of nuclear pre-mRNAs involved in stimulating cell growth, 38 including PKM2.…”
Section: Novel Links Between Pkm2 Hur P27 and Cell Cycle Arrestsupporting
confidence: 60%
“…The data presented here show that in control cells, pY-containing HuR is predominantly a nuclear protein, and that forms of PKM2 that retain pY-binding ability co-immunoprecipitate with HuR as well as rescue cells from defects in cell cycle progression caused by PKM2 knock-down. The accumulation of HuR in the cytoplasm following suppression of PKM2 levels also supports the idea that PKM2 binds and traps HuR, and in particular pY-containing HuR (as well as possibly p27 itself) 47 in the nucleus, limiting the ability of HuR to facilitate p27 mRNA translation in the cytoplasm. Under these conditions the trapped nuclear HuR may be able to function as a progrowth regulator of splicing and a stabilizer of nuclear pre-mRNAs involved in stimulating cell growth, 38 including PKM2.…”
Section: Novel Links Between Pkm2 Hur P27 and Cell Cycle Arrestsupporting
confidence: 60%
“…The different results might be related to the different time point after SCI because SCI includes complex physiological and biochemical mechanisms. Various proteins are increased immediately after SCI to compensate for the injury and then decreased with the passage of time [32]. Our results also showed that MDSCs could promote β -catenin, which is downregulated in injured neurons.…”
Section: Discussionsupporting
confidence: 52%
“…Both a PEP-dependent protein kinase activity of M 2 -PYK [24,134,151,207,[219][220][221][222][223][224][225][226][227][228][229] and a translocation of dimeric M 2 PYK into the nucleus to act as a transcription factor [34,73,120,125,[230][231][232][233][234][235] have been proposed for M 2 PYK. The protein kinase activity appears to primarily be detected in the nucleus using nuclear proteins as substrates.…”
Section: Pyk In Non-canonical Role: Nuclear Translocation Of M 2 Pyk To Act As a Protein Kinasementioning
confidence: 99%